Corrupted votes and rule compliance - Arno Apffelstaedt; Jan Freundt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Allegations of voter fraud accompany many real-world elections. How does electoral malpractice affect the acceptance of elected institutions? Using an online experiment in which people distribute income according to majority-elected rules, we show that those who experience vote buying or voter disenfranchisement during the election are subsequently less willing to comply with the rule. On average, the detrimental impact of electoral malpractice on compliance is of the same magnitude as removing the election altogether and imposing a rule exogenously. Our experiment shows how corrupting democratic processes can impact economic behavior and sheds light on the behavioral mechanisms underlying "rule legitimacy".
Keywords: D02; D72; D91; C92; 330; rule compliance; endogenous institutions; corruption; procedural fairness; legitimacy